(untitled) (Foro de Educacion, 2026)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) has been witnessed to integrate with the Project-Based Learning (PBL) in improving issues of concern with regard to vocational competencies and creativity. The broader meaning of STEAM-PBL in calligraphy is that it offers a platform to integrate technical knack and artistic ingenuity. The proposed study is intended to assess the efficacy of STEAM-PBL in the development of calligraphy vocational skills and the influence it has on artistic creativity, and to examine learning motivation as a mediator between STEAM-PBL and student outcomes. A structured questionnaire survey was adopted, and 150 respondents were enrolled in vocational calligraphy programs through a Likert scale (1-5). The statistical test used in data analysis included correlation, regression, and mediation analysis using SPSS. Findings showed that STEAM-PBL resulted in a significant improvement in vocational skills and artistic creativity in a calligraphic lesson, and learning motivation mediated this improvement. Both of those skills were directly and positively impacted by STEAM-PBL, and motivated students displayed greater creativity and technical accuracy. The article indicates how STEAM-PBL can be used to train vocational and artistic skills in the teaching of calligraphy. Learning motivation added to the teaching process may enhance the impact of STEAMPBL and hence offer useful data to teachers in creative disciplines.